Further investigation for the 18O + 40Ca, 76Se and 116Sn elastic scattering angular distributions - M. N. El-Hammamy; Awad A. Ibraheem; Sh. Hamada (Journal of Taibah University for Science, 2024)
At 275MeV energy, the efficiency of analysing the newly measured angular distributions for 18O ions elastically scattered from 40Ca, 76Se and 116Sn targets is examined using double and cluster folding models. Two choices for the imaginary potential part, phenomenological squared Woods Saxon (WS) and (double or cluster) folded forms, were implemented in the calculations. Different 18O density distributions, including its cluster structure (14C + α), were put forward for preparing the folding potentials of the considered systems. Furthermore, we investigated the impact of other channels coupling using two distinct methods: incorporating a dynamic polarization surface potential into non-renormalized cluster folded potentials, and  employing the continuum discrete coupled channels (CDCC) approach. To facilitate comparison, we also utilized the phenomenological optical model with real WS and imaginary squared WS potentials. The theoretical results demonstrated significant agreement with the experimental data, providing strong evidence for the efficacy of the methodologies under investigation.